2021
DOI: 10.3390/en14010210
|View full text |Cite
|
Sign up to set email alerts
|

The Energy of Finance in Refining of Medical Surge Capacity

Abstract: The availability of resources and their concentration in the place of greatest need, will not allow us to successfully overcome a medical surge without the energy required to activate these resources and activities, and increase their quantities if necessary, that is why the staff and management of healthcare institutions are forced to making ethical crisis decisions about who wins and who loses. This study highlights the versatility of the concept of ‘energy’ by attributing it to money or financial resources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
10
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 56 publications
0
10
0
2
Order By: Relevance
“…Therefore, based on the term "financial energy of the household," the author of this article understands the financial situation of the household and the ability to repay the debt, taking into account a wide range of financial, but also demographic and behavioral factors. Such a broad term of finance has already been applied in terms of refining the medical surge capacity [8] during the COVID-19 pandemic. The second example of interdisciplinary terms and research approaches in today's literature studies can be a theory of the "life cycle" that combines biological, economic, and engineering aspects into one compact study that analyzes the engineering and financial processes at different stages of enterprise development [9].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, based on the term "financial energy of the household," the author of this article understands the financial situation of the household and the ability to repay the debt, taking into account a wide range of financial, but also demographic and behavioral factors. Such a broad term of finance has already been applied in terms of refining the medical surge capacity [8] during the COVID-19 pandemic. The second example of interdisciplinary terms and research approaches in today's literature studies can be a theory of the "life cycle" that combines biological, economic, and engineering aspects into one compact study that analyzes the engineering and financial processes at different stages of enterprise development [9].…”
Section: Introductionmentioning
confidence: 99%
“…The interdisciplinary approach to financial energy (cf. [1]) allows for associating it with the general financial condition of the entity [2], which is influenced, among others, by the use of equity and external capital and the treatment of money as a source of energy [3]. Based on Korol [2,4], the paper adopts the concept of "financial energy of a farm" understood as its general financial situation.…”
Section: Introductionmentioning
confidence: 99%
“…These changes cause structural and other swings in various fields of society, in particular, the financial sector, which is one of the first to respond to global challenges. Thus, recent events related to the spread of coronavirus disease (COVID- 19) have clearly demonstrated that all markets around the world have reacted with different in value, but clearly significant changes in financial figures [3][4][5][6][7][8][9][10][11][12]. An important part of the financial sector of the economy is the insurance sector, which is integral to financial stability as a whole [13].…”
Section: Introductionmentioning
confidence: 99%